(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The main aim of the research is to identify the impact of the application of IFRS for SMEs on optimizing the utility of information for financial reports. To answer the questions and test the hypotheses of the research, researchers relied on the descriptive analytical approach. First, the researchers clarified the theoretical aspect through previous studies, and then they analyses d the results of the applied study by testing the hypothesis using the SPSS. A questionnaire was distributed after evaluation and arbitration by a number of specialists on selected sample. The sample of 120 respondents consists of general managers, department directors, head of departments, accountants, auditors and financial controllers working in the financial departments of the Palestinian and Libyan businesses. The results of the research showed a the implementation of IFRS has many advantages and benefits, the most important of which is improving the quality of disclosed financial information, and increasing the level of disclosure and transparency in financial reports. The study also recommended that small and medium-sized enterprises of the Palestinian and Libyan businesses should comply with the IFRS to improve the quality of information financial reports.